2010
DOI: 10.1097/acm.0b013e3181e10159
|View full text |Cite
|
Sign up to set email alerts
|

Variables Associated With Full-Time Faculty Appointment Among Contemporary U.S. Medical School Graduates: Implications for Academic Medicine Workforce Diversity

Abstract: Purpose The authors sought to identify variables independently associated with full-time faculty appointment among recent medical graduates. Method With institutional review board approval, the authors developed a database of individualized records for six midwestern medical schools’ 1997–2002 graduates. Using multivariate logistic regression, they identified variables independently associated with full-time faculty appointment from among demographic, medical-school-related, and career-intention variables. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 23 publications
3
40
1
Order By: Relevance
“…18 Recent research has shown that career preference for a full-time faculty position on the GQ is predictive of actually being appointed to such a position. 13 However, unlike Jeffe et al, 12 we did not find differences in academic medicine career interest by race and ethnicity. Our survey sample differed from that of Jeffe et al 12 in numerous ways, however; for example, ours had greater proportions of female respondents, of black and Hispanic respondents, and of respondents with medical education debt greater than $150,000.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…18 Recent research has shown that career preference for a full-time faculty position on the GQ is predictive of actually being appointed to such a position. 13 However, unlike Jeffe et al, 12 we did not find differences in academic medicine career interest by race and ethnicity. Our survey sample differed from that of Jeffe et al 12 in numerous ways, however; for example, ours had greater proportions of female respondents, of black and Hispanic respondents, and of respondents with medical education debt greater than $150,000.…”
Section: Discussionmentioning
confidence: 46%
“…Additionally, Andriole and colleagues 13 found that among recent medical school graduates, being female or an MD-PhD program graduate was independently associated with a greater likelihood of full-time faculty appointment, whereas race and ethnicity were not. Little else is known about when, why, and how racial and ethnic minority medical students make their decisions about academia.…”
Section: Research Reportmentioning
confidence: 97%
“…20 Private philanthropic organizations similarly are starting to analyze awardee data to address these issues. 21 The percentage of CSDA applicants, for example, from different racial and ethnic groups is similar to estimates of that of full-time medical faculty, 22 but some racial and ethnic groups remain underrepresented as compared with the U.S. population. 23 Still, the percentage of underrepresented minorities in the CSDA applicant pool is similar to that of the K23 applicant pool.…”
Section: Characteristics Of Successful and Unsuccessful Applicantsmentioning
confidence: 82%
“…15-21 However, few control group studies of practicing physicians have evaluated long-term outcomes of PBPs such as what patient populations are served by PBP physician alumni. 22-23 …”
mentioning
confidence: 99%
“…22-23 The first study by McDougle, et al found that physicians who were graduates of Ohio State University’s (OSU’s) PBP were more likely than their control group counterparts to be practicing medicine in federally designated medically underserved areas (29.4% versus 5.1%, p≤.01) or to be providing services where 40% or more of the patients were medically indigent or poor (67.6% versus 33.3%, p≤.01). 22 The second study by Lupton, et al, found that alumni from five premedical postbaccalaureate programs across the University of California system (UCPB) were more likely than their control group counterparts to enter primary care (53.1% versus 40.1%, p≤.001), and work in high-poverty communities (16.2% versus 8.7%, p≤.05), high-Latino communities (18.3% versus 8.7%, p≤.01), or high-African American communities (29.8% versus 19.8%, p≤.02). 23 …”
mentioning
confidence: 99%